Opportunities and Challenges of Implementing Artificial Intelligence (AI) in Human Resource Management at the Sales and Marketing Department of Royal Ambarrukmo Yogyakarta, Indonesia - Karmin, Enny (Technium Social Sciences Journal, 2025)
The application of Artificial Intelligence (AI) in the hospitality industry presents both opportunities and challenges for human resources in the Sales and Marketing Department. This study aims to analyze how human resources at Royal AmbarrukmoYogyakarta cope with the digital transformation in the era of AI. The research employs a descriptive qualitative method, utilizing in-depth interviews, observations, and document studies. The data collected is analyzed using the interactive model approach by Miles and Huberman (1994), which involves three main stages: data reduction, data display, and conclusion drawing and verification. The findings indicate that AI enhances operational efficiency and service personalization but faces challenges such as employee resistance and a digital skills gap. Continuous training strategies and adaptive AI integration are essential for the successful implementation of this technology.